The Boss of It All. - Trier, Lars von (Oberon Books, 2014)
A critically acclaimed, smart and fast-paced comedy about faked identities and explosive office politics, adapted from Lars von Trier's cult classic film. The boss of an IT company is secretly selling up. To save face he hires Kristoffer, an actor, to take the blame. Thrown in at the deep end, the hapless actor gets more than he bargained for. In an office of misfit staff, he faces an unexpected dilemma; to sell off the company or try and save his new-found friends. Through 40 years of making and touring exceptional and original theatre, New Perspectives has established itself as the East Midlands national touring company. This is Jack McNamara's first adaptation as the company's Artistic Director.